Real‐time flow MRI of the aorta at a resolution of 40 msec. Issue 1 (11th October 2013) - Joseph, Arun; Kowallick, Johannes T.; Merboldt, Klaus‐Dietmar; Voit, Dirk; Schaetz, Sebastian; Zhang, Shuo; Sohns, Jan M.; Lotz, Joachim; Frahm, Jens
<x xml:space="preserve">Abstract</x> Purpose To evaluate a novel real‐time phase‐contrast magnetic resonance imaging (MRI) technique for the assessment of through‐plane flow in the ascending aorta. Materials and Methods Real‐time MRI was based on a radial fast low‐angle shot (FLASH) sequence with about 30‐fold undersampling and image reconstruction by regularized nonlinear inversion. Phase‐contrast maps were obtained from two (interleaved or sequential) acquisitions with and without a bipolar velocity‐encoding gradient. Blood flow in the ascending aorta was studied in 10 healthy volunteers at 3 T by both real‐time MRI (15 sec during free breathing) and electrocardiogram (ECG)‐synchronized cine MRI (with and without breath holding). Flow velocities and stroke volumes were evaluated using standard postprocessing software. Results The total acquisition time for a pair of phase‐contrast images was 40.0 msec (TR/TE = 2.86/1.93 msec, 10° flip angle, 7 spokes per image) for a nominal in‐plane resolution of 1.3 mm and a section thickness of 6 mm. Quantitative evaluations of spatially averaged flow velocities and stroke volumes were comparable for real‐time and cine methods when real‐time MRI data were averaged across heartbeats. For individual heartbeats real‐time phase‐contrast MRI resulted in higher peak velocities for values above 120 cm s−1. Conclusion Real‐time phase‐contrast MRI of blood flow in the human aorta yields functional parameters for individual heartbeats. When averaged across heartbeats real‐time flow velocities and stroke volumes are comparable to values obtained by conventional cine MRI. J. Magn. Reson. Imaging 2014;40:206–213. © 2013 Wiley Periodicals, Inc.